A Dual Approach to Exercising Statutory Supervision over Hospitals in Poland - Kautsch, Marcin (Journal of Public Governance, 2021)
Objectives: The paper aims to describe the current model of supervision over public hospitals in Poland. Research Design & Methods: The paper is based on a scoping review and content analysis of applicable legislation, their resumes, and pertinent data sourced from the Internet, including articles, reports, and dedicated websites. The sourced data was identified with the aid of the Google search engine. All assembled source materials were subsequently filtered out in terms of their suitability for the subject matter under scrutiny, and assessed in line with the key assumptions of the agency theory, whereby an agent is entrusted by the principal with the task of managing an organisation. Findings: Polish hospitals operate either as the so-called autonomous public healthcare units, or as commercial companies. Both forms are publicly owned and invested with identical scope of statutory tasks, whereas their supervision remainssubject to different statutory regulations. However, the organisational models presently in place do not actually provide for an effective securing of the key supervisory objectives. Implications / Recommendations: A general structural overhaul is therefore postulated, with a view to introducing more effective, in-house-developed supervisory solutions, especially with regard to autonomous public hospitals. Article classification: research article